Challenging HIV-related stigma and discrimination: the role of the family life educator - Asiedu, Gladys B. (Kansas State University, 2007)
Today the HIV/AIDS epidemic is one of the many crises families may face. Many people have died of the disease while others are still living with it. At the end of 2003, an estimated 1,039,000 to 1,185,000 persons in the United States were living with HIV/AIDS, with 24-27% undiagnosed and unaware of their HIV infection. The Centers for Disease Control (CDC) estimates that approximately 40,000 persons become infected with HIV each year (CDC, 2007). Stigmatization and discrimination related to HIV/AIDS is one of the many challenges that individuals and families affected by the disease face. They are unable to get employment, are denied health care, cannot access services in their communities and sometimes lose respect and power as a result of stigma. Stigma and discrimination also have been recognized as one of the main obstacles to HIV/AIDS, testing, prevention and treatment and yet little has been done to combat it. Stigma and discrimination is not only experienced by people living with HIV/AIDS but their family members, close friends, service providers and people that work with them also are stigmatized by association. This report highlights the need for family life educators to expand HIV educational programs to include issues on stigmatization and discrimination. It identifies some of the reasons why people stigmatize, the ways which stigma and discrimination are expressed and the impacts it has on individuals and their family members. Using Bronfenbrenner’s ecological model of human development, this report identifies the need to look at HIV-related stigma and discrimination as a societal problem rather than individual problem, and presents implications for education programs for the general public.
Keywords: Acquired immune deficiency syndrome Human immunodeficiency virus People living with AIDS; Discrimination HIV/AIDS and stigma Role of family life educator; Sociology, Individual and Family Studies (0628)